The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fenrg.2019.00031
|View full text |Cite
|
Sign up to set email alerts
|

Social Innovation in Community Energy in Europe: A Review of the Evidence

Abstract: Citizen-driven Renewable Energy (RE) projects of various kinds, known collectively as community energy (CE), have an important part to play in the worldwide transition to cleaner energy systems. On the basis of evidence from 8 European countries, we investigate CE, over approximately the last 50 years (c.1970-2018), through the lens of Social Innovation (SI). We carry out a detailed review of literature around the social dimension of renewable energy; we collect, describe and map CE initiatives from Belgium, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0
11

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(136 citation statements)
references
References 72 publications
(117 reference statements)
1
95
0
11
Order By: Relevance
“…Given the perils of oversimplification and generalizing when explaining the current low incidence of CE in PSECs, with literature on the topic quite scarce [7,13], and uncertainty about the membership of new and/or small organizations in the European federation REScoop.eu [12], we decided to perform an exploratory overview at a country level. The following three steps were applied with the aim of performing a clustering of the development level of CE and RES cooperatives in PSECs:…”
Section: Exploratory Overview Of Countries and Clustering 21 Methodologymentioning
confidence: 99%
See 3 more Smart Citations
“…Given the perils of oversimplification and generalizing when explaining the current low incidence of CE in PSECs, with literature on the topic quite scarce [7,13], and uncertainty about the membership of new and/or small organizations in the European federation REScoop.eu [12], we decided to perform an exploratory overview at a country level. The following three steps were applied with the aim of performing a clustering of the development level of CE and RES cooperatives in PSECs:…”
Section: Exploratory Overview Of Countries and Clustering 21 Methodologymentioning
confidence: 99%
“…According to its statutes it aims to support local farmers [42]. However, a recent review concluded that this project "seems to be an initiative arising from the business sector, rather than a bona fide citizens' movement" [13]. Another RES cooperative, Polska Spóldzielnia Energetycna, is registered in Bielsko Biala, but it is doubtful if it still operates.…”
Section: Polandmentioning
confidence: 99%
See 2 more Smart Citations
“…With the increase of WTI oil prices, cleaner energies, such as electricity and natural gas, offer some alternative products for consumers. Additionally, the attitude of policy gives guidance to households, encouraging them to turn their attention to alternative products and, consequently, changing the relationships between WTI oil prices and both the CPI and MCPI (Hewitt et al, 2019). On the other hand, the diverse passthrough to the CPI and MCPI is heavily dependent on their characteristics; for instance, this result indicated the existence of diverse share prices.…”
Section: Non-linear Frameworkmentioning
confidence: 99%